2021
DOI: 10.1177/1358863x20983475
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the role of heat therapy for patients with intermittent claudication due to peripheral artery disease

Abstract: Intermittent claudication (IC) is associated with impairments in quality of life and walking ability. Heat therapy is an emerging cardiovascular therapy, which may improve walking in patients with IC. We undertook a systematic review to establish current evidence for heat therapy for patients with IC. We searched five databases (Ovid Medline / PubMed, Embase, Scopus / Web of Science, Cochrane Library and Health Technology Assessment Databases). A total of 6751 records were screened with 76 full-text articles a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Results of a quiet recent systematic review [30] were not aligned with the current review results as it suggested signi cant differences in the 6MWT, the possible reason is that they did pooled the studies together and one or two studies could not be sure about the results, they did not measure the difference between the PAD and control groups, and they reported that their results could not give clear conclusions for patients with PAD due to small number of studies and large heterogeneity between the types of the interventions in the intervention and control groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of a quiet recent systematic review [30] were not aligned with the current review results as it suggested signi cant differences in the 6MWT, the possible reason is that they did pooled the studies together and one or two studies could not be sure about the results, they did not measure the difference between the PAD and control groups, and they reported that their results could not give clear conclusions for patients with PAD due to small number of studies and large heterogeneity between the types of the interventions in the intervention and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review assessed the effect of heat therapy on arterial shear rate, blood ow rate, systolic blood pressure (SBP), diastolic blood pressure (DBP), six-minute walk test (6MWT) and ABI in patients with PAD and intermittent claudication. There was no comparison between the intervention and control groups and there was no pooled data in different outcomes in this systematic review [30]. The recent review showed that the 6MWT distance was improved only in whole body immersion in patient with PAD, but a recent randomized controlled trial (RCT) showed non-signi cant difference in the 6MWT distance between the supervised exercise and the heat therapy procedures [9].…”
Section: Introductionmentioning
confidence: 95%